High-strength corrosion-resistant ecological ceramic plate and preparation process thereof

By optimizing the raw material formula and preparation process of the ceramic plate, combined with smelting iron ore tailings, sludge and alkali-resistant glass fiber and other materials, the problem of insufficient strength and corrosion resistance of the ceramic plate is solved, and the high strength and corrosion resistance of the ceramic plate are achieved. Enhanced its security and application breadth.

CN119430861AActive Publication Date: 2025-02-14FUJIAN HUATAI GROUP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411460570.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing ceramic plates have shortcomings in strength and corrosion resistance, are highly brittle and have weak impact resistance, and are prone to fracture and corrosion problems during use, which poses safety hazards.

Method used

The raw materials such as smelting iron ore tailings, sludge, alkali-resistant glass fiber and clay powder are combined with specific plasticizers and process methods, including crushing, mixing, wet material preparation, vacuum extrusion molding, drying and sintering, etc. Optimize the formula and preparation process of ceramic plates.

Benefits of technology

It significantly improves the strength and corrosion resistance of ceramic plates, enhances its impact resistance and use safety, and makes ceramic plates more safe and widely used in application and construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091751020000091
    Figure BDA0005091751020000091
  • Figure BDA0005091751020000101
    Figure BDA0005091751020000101
  • Figure BDA0005091751020000102
    Figure BDA0005091751020000102
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a high-strength corrosion-resistant ecological ceramic plate which comprises the following raw materials: 80-85 parts of pottery clay powder, 2-5 parts of smelted iron ore tailings, 5-8 parts of alkali-resistant glass fibers, 2-5 parts of sludge, 1-2 parts of clay powder and 0.2-0.4 part of a plasticizer. The invention further discloses a preparation process of the ceramic plate, in the preparation process, the drying process, the sintering process and the cooling process all adopt a stepped temperature mode, the characteristics of a green body can be combined, and the quality defects such as cracks and bending of the prepared pottery clay are reduced. On the basis that the cost is not increased, raw material optimization and a preparation process are innovated, and the strength and corrosion resistance of the ceramic plate are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of building materials, and specifically relates to a high-strength, corrosion-resistant ecological ceramic plate and a preparation process thereof. Background Art

[0002] Ceramic panels are a new type of curtain wall material in today's construction industry. They are environmentally friendly and energy-saving, moisture-proof, breathable and sound-insulating, rich in color, durable and new, and have a wide range of applications. It organically combines traditional materials with modern architecture, provides a more flexible facade design solution for design applications, and is conducive to the beautification of cities and the living of buildings. At present, the materials on the market use pure clay from nature as raw materials, add a small amount of quartz, pumice, feldspar and other ingredients such as colorants, and are formed by high-pressure extrusion, low-temperature drying and high-temperature firing at 1200℃-1250℃. They are green, environmentally friendly, radiation-free, mild in color, and will not cause light pollution.

[0003] The rise of clay panels has brought about a large demand for natural clay. However, clay resources are limited after all, and the mining of clay will inevitably cause damage to nature. Therefore, this technical field has begun to explore the use of sludge, waste ceramics or iron ore tailings as raw materials for clay panels. For example, "CN1027958381A" discloses a low-temperature, fast-fired environmentally friendly clay panel prepared using iron ore tailings and its preparation method, and "CN103896556A" discloses a new type of environmentally friendly and energy-saving curtain wall material made of sludge and waste ceramics. However, the preparation process of the ceramic panels in the above two technical solutions adopts a one-step firing method. Through application practice, it is found that the finished products are brittle and have low corrosion resistance. Ceramic panels are stronger than natural stones, but like natural stones, they are brittle materials with weak impact resistance. Theoretically, the technical indicators of ordinary ceramic panel installation methods meet the requirements, but due to the discreteness of the production and installation process, as well as the existence of other uncontrollable factors, there is a possibility of accidental breakage, fragmentation (such as collision with hard objects when cleaning the curtain wall) and falling during use. In addition, ceramic panels are used in open curtain walls, mostly high-rise building curtain walls and even super high-rise buildings. They are exposed to long-term corrosion and flooding in strong winds and rainstorms, and there is a possibility of falling during use. Therefore, higher requirements are placed on the strength and corrosion resistance of ceramic panels, otherwise there will be great safety hazards.

[0004] The machine nozzle is the final extrusion forming port of the ceramic plate blank. It promotes the compact synthesis of the clay into a brick and tile blank. Its main function is to obtain a blank with high density, good mechanical strength, smooth surface, low water content and a certain shape and size. The larger the flow area of ​​the inner cavity of the machine nozzle and the smoother the surface, the more conducive it is to the flow of ceramic clay, and the less extrusion forming force is required. On the contrary, the smaller the flow area of ​​the inner cavity of the machine nozzle and the rough and uneven surface, the mud flow is hindered, and the required extrusion forming force is greater. Process modification from the extrusion port is also a research direction for improving the quality of ceramic plates.

[0005] Therefore, improving the strength and corrosion resistance of ceramic panels is a research topic that technicians in this field need to continue to carry out. Summary of the invention

[0006] The present invention aims to improve the strength and corrosion resistance of ceramic panels, and innovates in terms of raw material optimization and preparation technology without increasing costs.

[0007] The specific technical solutions are as follows:

[0008] A high-strength, corrosion-resistant ecological ceramic plate. The raw materials of the ceramic plate include 80-85 parts of clay powder, 2-5 parts of iron ore tailings, 5-8 parts of alkali-resistant glass fibers, 2-5 parts of sludge, 1-2 parts of clay powder, and 0.2-0.4 parts of plasticizer, calculated by weight.

[0009] Preferably, the clay powder is one or more of kaolinite, illite or montmorillonite, based on mass percentage.

[0010] Preferably, the components of the iron ore smelting tailings are (mass percentage): SiO2: 61.2% to 70%, Fe2O3, 6% to 9%, Al2O3: 15% to 20%, MgO: 1% to 4%, CaO: 0.5% to 4.5%, TiO2: 0.2 to 1.5%, K2O: 0.5 to 2.5%, Na2O: 0.1% to 4%, and the balance is carbon.

[0011] Preferably, the sludge has an organic matter content of 3%-12% and a sand content of 1-6%.

[0012] Preferably, the plasticizer is water glass.

[0013] Preferably, the raw materials of the ceramic plate include 83 parts of clay powder, 4 parts of iron ore smelting tailings, 6 parts of alkali-resistant glass fiber, 4 parts of sludge, 1 part of clay powder, and 0.3 parts of plasticizer, calculated by mass.

[0014] The preparation process of the high-strength corrosion-resistant ecological ceramic plate comprises the following steps:

[0015] (1) according to the proportion, clay powder, iron ore tailings, and alkali-resistant glass fiber are taken and crushed to a size of more than 200 meshes, and then sludge, clay powder, and plasticizer are added to form a mixed raw material;

[0016] (2) mixing the mixed raw materials and water in a mixer in a ratio of 15% to 20% of the mixed raw materials, thereby preparing a wet material;

[0017] (3) feeding the wet material into a mud mill for mixing, thereby obtaining a mud material with a plasticity index of 9-12;

[0018] (4) feeding the above-mentioned clay material into a vacuum extruder and molding it through a machine mouth die. During extrusion, the titanate graphene mixed solution is dynamically and continuously injected into the inner surface of the machine mouth die. After the clay material is extruded, it is cut into corresponding specifications to obtain a wet body. The flow rate of the titanate graphene mixed solution is 2-3 ml / m2;

[0019] (5) drying the wet green body at a temperature of 40° C. to 150° C. for 4 to 8 hours to obtain a dry green body;

[0020] (6) The dried green body is sent to a firing kiln and sintered at a temperature of 1000°C-1140°C for 3-5 hours.

[0021] (7) Cool the ceramic plate.

[0022] Preferably, the method for preparing the titanate graphene mixed solution in the above process step (4) is: completely dispersing graphene oxide in water, adding a titanate coupling agent and mixing evenly to obtain a mixed solution, the viscosity of the mixed solution is 2000-4000cps (25°C), and the mass ratio of graphene oxide to titanate coupling agent is 4:1-2.

[0023] Preferably, the drying method of the above process step (5) is: first drying at 40-50°C for 3-5 hours, then drying at 51-80°C for 0.5-2 hours, and then drying at 81-150°C for 0.5-1 hour, and the sintering method of step (6) is: 1-2 hours at 1000-1050°C, and 2-3 hours at 1051-1140°C.

[0024] Preferably, the cooling method of the above process step (7) is: transfer the ceramic plate to a cooling room, cool the ceramic plate to 300-600°C, maintain the ambient temperature at 200-300°C for 2-3 hours, reduce the ambient temperature to 100-200°C for 2-3 hours, and then cool naturally.

[0025] The beneficial effects of the present invention are:

[0026] (1) The present invention uses industrial solid waste iron ore tailings and sludge combined with ceramic wood powder as raw material components to prepare ceramic panels, and combines glass fiber at the same time. The raw materials of this technical solution use a high-silicon, low-aluminum, high-potassium-sodium formula system and a specific plasticizer to optimize the ceramic panel formula, improve the fluidity of the ceramic panel mud, and facilitate the extrusion forming of the ceramic panel blank. The ceramic panel finally prepared has high strength and good corrosion resistance, which greatly improves the performance of the ceramic panel, making it safer and more widely used in the application and construction process.

[0027] (2) When the content of plastic material in the raw material formula is high, the required extrusion molding pressure is low, but the green body drying and sintering shrinkage deformation is large; on the contrary, when the content of plastic material in the ceramic raw material formula is low, that is, when the content of barren material is high, the green body drying and sintering shrinkage deformation is small, but the required extrusion molding pressure is high. The plastic material and barren material ratio range in the raw material formula of the present invention is appropriate, and the pressure required for extrusion molding and the green body drying and sintering shrinkage deformation are moderate.

[0028] (3) In the preparation process described in the present invention, the drying, sintering and cooling processes all adopt a step-by-step temperature method, which can be combined with the characteristics of the green body to reduce quality defects such as cracks and bending in the prepared clay.

[0029] (4) Surface treatment of ceramic substrates is a key step in improving the quality and performance of ceramic substrates. In this technical solution, a titanate-graphene mixed solution is dynamically injected into the extrusion mold during the extrusion process, which can reduce the interference of the mold surface on the ceramic surface and help to ease the extrusion pressure of the mud material, making the surface of the ceramic substrate smoother and cleaner. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with the examples and comparative examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0031] In the following examples, the alkali-resistant glass fiber was purchased from Hejian Xinlong Glass Fiber Products Co., Ltd., the sludge came from the Dongli Lake Southern Sewage Treatment Plant, and the clay powder was purchased from Guangzhou Yifeng Chemical Technology Co., Ltd.

[0032] Example 1

[0033] Raw material formula: 83 parts of clay powder, a mixture of kaolinite, illite and montmorillonite in a mass ratio of 1:1:1, 4 parts of iron ore tailings, 6 parts of alkali-resistant glass fiber, 4 parts of sludge, 1 part of clay powder, and 0.3 parts of sodium water glass. The iron ore tailings are composed of (by mass percentage): SiO2: 65%, Fe2O3, 8%, Al2O3: 18%, MgO: 2%, CaO: 2%, TiO2: 1%, K2O: 2%, Na2O: 2%, and the balance is carbon. The sludge has an organic matter content of 8% and a sand content of 5%.

[0034] (1) according to the proportion, clay powder, iron ore tailings, and alkali-resistant glass fiber are taken and crushed to a size of more than 200 meshes, and then sludge, clay powder, and water glass are added to form a mixed raw material;

[0035] (2) mixing the mixed raw materials and water in a mixer in a ratio of 18% by weight of the mixed raw materials to obtain a wet material;

[0036] (3) feeding the wet material into a clay mill for mixing to obtain a clay material having a plasticity index of 10;

[0037] (4) feeding the above-mentioned clay material into a double-shaft vacuum extruder to be formed through a die, and then cutting into the same specification of 400 mm×400 mm, thereby obtaining a wet green body;

[0038] (5) Dry the wet body at 45°C for 4 hours, then at 70°C for 1 hour, and then at 120°C for 1 hour.

[0039] (6) The dried body is sent to a firing kiln at 1050°C for 1.5 hours and at 1140°C for 2.5 hours.

[0040] (7) The ceramic plate is transferred to a cooling room, the temperature of the ceramic plate is reduced to 600°C, the ambient temperature is maintained at 300°C for 3 hours, the ambient temperature is reduced to 100°C for 3 hours, and then naturally cooled to obtain the finished product.

[0041] Example 2

[0042] Raw material formula: by weight, 85 parts of clay powder of a mixture of illite and montmorillonite in a mass ratio of 1:1, 3 parts of smelting iron ore tailings, 5 parts of alkali-resistant glass fiber, 2 parts of sludge, 1.5 parts of clay powder, and 0.4 parts of water glass. The components of the smelting iron ore tailings are (mass percentage): SiO2: 70%, Fe2O3, 7%, Al2O3: 17%, MgO: 3%, CaO: 3%, TiO2: 1.5%, K2O: 2.5%, Na2O: 4%, and the balance is carbon. The sludge contains 12% organic matter and 2% sand.

[0043] (1) according to the proportion, clay powder, iron ore tailings, and alkali-resistant glass fiber are taken and crushed to a size of more than 200 meshes, and then sludge, clay powder, and water glass are added to form a mixed raw material;

[0044] (2) mixing the mixed raw materials and water in a mixer in a ratio of 15% of the weight of the mixed raw materials to obtain a wet material;

[0045] (3) feeding the wet material into a clay mill for mixing to obtain a clay material having a plasticity index of 11;

[0046] (4) feeding the above-mentioned clay material into a double-shaft vacuum extruder to be formed through a die, and then cutting into the same specification of 400 mm×400 mm, thereby obtaining a wet green body;

[0047] (5) Dry the wet body at 50°C for 4 hours, then at 80°C for 2 hours, and then at 150°C for 1 hour.

[0048] (6) The dried body is sent to a firing kiln at 1000°C for 2 hours and at 1140°C for 3 hours.

[0049] (7) The ceramic plate is transferred to a cooling room, the temperature of the ceramic plate is reduced to 500°C, the ambient temperature is maintained at 250°C for 2.5 hours, the ambient temperature is reduced to 200°C for 2 hours, and then naturally cooled to obtain the finished product.

[0050] Example 3

[0051] Raw material formula: by weight, 80 parts of kaolinite, illite and montmorillonite mixture clay powder, 5 parts of iron ore tailings, 8 parts of alkali-resistant glass fiber, 2 parts of sludge, 1.5 parts of clay powder, 0.2 parts of water glass. The iron ore tailings components are (mass percentage): SiO2: 62%, Fe2O3, 6%, Al2O3: 15%, MgO: 1%, CaO: 0.5%, TiO2: 0.2%, K2O: 0.5%, Na2O: 0.1%, and the balance is carbon. The sludge has an organic matter content of 8% and a sand content of 5%.

[0052] (1) according to the proportion, clay powder, iron ore tailings, and alkali-resistant glass fiber are taken and crushed to a size of more than 200 meshes, and then sludge, clay powder, and water glass are added to form a mixed raw material;

[0053] (2) mixing the mixed raw materials and water in a mixer in a ratio of 15% of the weight of the mixed raw materials to obtain a wet material;

[0054] (3) feeding the wet material into a clay mill for mixing to obtain a clay material having a plasticity index of 9;

[0055] (4) feeding the above-mentioned clay material into a double-shaft vacuum extruder to be formed through a die, and then cutting into the same specification of 400 mm×400 mm, thereby obtaining a wet green body;

[0056] (5) The wet body was first dried at 40°C for 5 hours, then at 55°C for 0.5 hour, and then at 85°C for 0.5 hour.

[0057] (6) The dried body is sent to a firing kiln at 1000°C for 1 hour and at 1100°C for 2 hours.

[0058] (7) The ceramic plate is transferred to a cooling room, the temperature of the ceramic plate is reduced to 300°C, the ambient temperature is maintained at 300°C for 3 hours, the ambient temperature is reduced to 100°C for 3 hours, and then naturally cooled to obtain the finished product.

[0059] Comparative Example 1 (single raw material)

[0060] Raw material formula: by mass, a mixture of kaolinite, illite and montmorillonite in a mass ratio of 1:1:1, 87 parts of clay powder and 3 parts of clay powder.

[0061] (1) According to the proportion, the clay powder is crushed to more than 200 meshes, and then the clay powder is formed into a mixed raw material;

[0062] (2) mixing the mixed raw materials and water in a mixer in a ratio of 18% by weight of the mixed raw materials to obtain a wet material;

[0063] (3) feeding the wet material into a clay mill for mixing to obtain a clay material having a plasticity index of 10;

[0064] (4) feeding the above-mentioned clay material into a double-shaft vacuum extruder to be formed through a die, and then cutting into the same specification of 400 mm×400 mm, thereby obtaining a wet green body;

[0065] (5) Dry the wet body at 45°C for 4 hours, then at 70°C for 1 hour, and then at 120°C for 1 hour.

[0066] (6) The dried body is sent to a firing kiln at 1050°C for 1.5 hours and at 1140°C for 2.5 hours.

[0067] (7) The ceramic plate is transferred to a cooling room, the temperature of the ceramic plate is reduced to 600°C, the ambient temperature is maintained at 300°C for 3 hours, the ambient temperature is reduced to 100°C for 3 hours, and then naturally cooled to obtain the finished product.

[0068] Comparative Example 2 (Direct Sintering)

[0069] Raw material formula: by mass, illite and montmorillonite mass ratio 1:1 mixture of clay powder 85 parts, smelting iron ore tailings 3 parts, alkali-resistant glass fiber 5 parts, sludge 2 parts, clay powder 1.5 parts, water glass 0.4 parts. The smelting iron ore tailings components are (mass percentage): SiO2: 70%, Fe2O3, 7%, Al2O3: 17%, MgO: 3%, CaO: 3%, TiO2: 1.5%, K2O: 2.5%, Na2O: 4%, the balance is carbon. The sludge organic matter content is 12%, sand content is 2%.

[0070] (1) according to the proportion, clay powder, iron ore tailings, and alkali-resistant glass fiber are taken and crushed to a size of more than 200 meshes, and then sludge, clay powder, and water glass are added to form a mixed raw material;

[0071] (2) mixing the mixed raw materials and water in a mixer in a ratio of 18% by weight of the mixed raw materials to obtain a wet material;

[0072] (3) feeding the wet material into a clay mill for mixing to obtain a clay material having a plasticity index of 10;

[0073] (4) feeding the above-mentioned clay material into a double-shaft vacuum extruder to be formed through a die, and then cutting into the same specification of 400 mm×400 mm, thereby obtaining a wet green body;

[0074] (5) Dry the wet body directly at 120°C for 3 hours.

[0075] (6) The dried body is sent to a firing kiln at 1140°C for 4 hours.

[0076] (7) Natural cooling.

[0077] In the following embodiments, when extruding the mud material, a titanate graphene mixed solution is dynamically and continuously injected into the inner surface of the die of the machine nozzle. The preparation method of the titanate graphene mixed solution is as follows: graphene oxide is dispersed in water, and a titanate coupling agent (LK-105, Guangzhou Longkai Chemical Co., Ltd.) is added to mix to obtain a mixed solution. The viscosity of the mixed solution is 3000-cps (25°C), and the mass ratio of graphene oxide to titanate coupling agent is 4:1.5. The amount of water added is regulated according to the viscosity.

[0078] Example 4

[0079] The improvement over Example 1 lies in that step (4) is: feeding the above-mentioned mud into a vacuum extruder and molding it through a machine nozzle die, and while extruding, dynamically and continuously injecting a titanate graphene mixed solution into the inner surface of the machine nozzle die, and the flow rate of the titanate graphene mixed solution is 2 ml / m2. After the mud is extruded, it is cut into corresponding specifications to obtain a wet blank; the rest is the same as Example 1.

[0080] Example 5

[0081] The improvement over Example 2 lies in that step (4) is: feeding the above-mentioned mud into a vacuum extruder and molding it through a machine nozzle die. During extrusion, a titanate graphene mixed solution is dynamically and continuously injected into the inner surface of the machine nozzle die. The flow rate of the titanate graphene mixed solution is 3 ml / m2. After extrusion, the mud is cut into corresponding specifications to obtain a wet blank. The rest is the same as Example 2.

[0082] Example 6

[0083] The improvement over Comparative Example 1 lies in that step (4) is: feeding the above-mentioned mud into a vacuum extruder for molding through a machine nozzle die, and while extruding, dynamically and continuously injecting a titanate graphene mixed solution into the inner surface of the machine nozzle die, wherein the flow rate of the titanate graphene mixed solution is 2 ml / m2, and the mud is cut into corresponding specifications after extrusion, thereby obtaining a wet blank; the rest is the same as Comparative Example 1.

[0084] Example 7

[0085] The improvement over Comparative Example 2 lies in that step (4) is: feeding the above-mentioned mud into a vacuum extruder for molding through a machine nozzle die, and while extruding, dynamically and continuously injecting a titanate graphene mixed solution into the inner surface of the machine nozzle die, wherein the flow rate of the titanate graphene mixed solution is 2 ml / m2, and the mud is cut into corresponding specifications after extrusion to obtain a wet blank; the rest is the same as Comparative Example 2.

[0086] The samples prepared in Examples 1-7 and Comparative Examples 1-2 were tested for performance using the industry standard JG / T324-2011 "Ceramic panels for building curtain walls" of the People's Republic of China's construction industry standard. The test items included surface quality, size and shape deviation, and performance. The number of samples with valid test results for each item was 10. For items that would not affect each other's test results, the samples could be reused.

[0087] (1) Surface quality inspection

[0088] According to the conditions specified in GB / T3810.2, a visual inspection was carried out at a distance of 1 m from the sample surface, and a measuring tool with an accuracy of no more than 0.1 mm was used for measurement, and the test results described in Table 1 were obtained.

[0089] Table 1 Surface quality test results of samples prepared in Examples 1 to 7 and Comparative Examples 1-2

[0090]

[0091]

[0092] As can be seen from the above table, from the aspect of surface detection, the clay prepared by Examples 1-3 and Comparative Example 1 fully meets the standard requirements, Comparative Example 1 also meets the requirements, Comparative Example 2 has more defects, and Comparative Example 3 has fewer defects.

[0093] (2) Performance index testing

[0094] The water absorption, bending strength, elastic modulus, frost resistance, thermal shock resistance, glaze crack resistance and chemical corrosion resistance were tested using the industry standard JG / T324-2011, and the test results shown in Table 2 were obtained.

[0095] Table 2 Performance index test results of samples prepared in Examples 1 to 3 and Comparative Examples 1-2

[0096]

[0097]

[0098] From the above experiments, it can be seen that the present invention uses industrial solid waste iron ore tailings and sludge combined with ceramic wood powder as raw material components to prepare ceramic panels, and combines glass fiber and a specific plasticizer, as well as the optimization of the process method to finally prepare ceramic panels with high strength and good corrosion resistance, thereby greatly improving the performance of the ceramic panels.

Claims

1. A high-strength, corrosion-resistant ecological ceramic plate, characterized in that: Calculated by weight, the raw materials of the ceramic plate include 80-85 parts of clay powder, 2-5 parts of iron ore tailings, 5-8 parts of alkali-resistant glass fiber, 2-5 parts of sludge, 1-2 parts of clay powder, and 0.2-0.4 parts of plasticizer.

2. According to claim 1, a high-strength, corrosion-resistant ecological ceramic plate is characterized in that: Calculated by weight, the clay powder is one or more of kaolinite, illite or montmorillonite.

3. According to claim 1, a high-strength, corrosion-resistant ecological ceramic plate is characterized in that: The iron ore smelting tailings has the following components in percentage by mass: SiO2: 61.2% to 70%, Fe2O3: 6% to 9%, Al2O3: 15% to 20%, MgO: 1% to 4%, CaO: 0.5% to 4.5%, TiO2: 0.2 to 1.5%, K2O: 0.5 to 2.5%, Na2O: 0.1% to 4%, and the remainder is carbon.

4. According to claim 1, a high-strength, corrosion-resistant ecological ceramic plate is characterized in that: The sludge has an organic matter content of 3%-12% and a sand content of 1-6%.

5. The high-strength, corrosion-resistant ecological ceramic plate according to claim 1, characterized in that: The plasticizer is water glass.

6. The high-strength, corrosion-resistant ecological ceramic plate according to claim 1, characterized in that: Calculated by weight, the raw materials of the ceramic plate include 83 parts of clay powder, 4 parts of iron ore smelting tailings, 6 parts of alkali-resistant glass fiber, 4 parts of sludge, 1 part of clay powder, and 0.3 parts of plasticizer.

7. A process for preparing the high-strength, corrosion-resistant ecological ceramic plate according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) according to the proportion, clay powder, iron ore tailings, and alkali-resistant glass fiber are taken and crushed to a size of more than 200 meshes, and then sludge, clay powder, and plasticizer are added to form a mixed raw material; (2) mixing the mixed raw materials and water in a mixer in a ratio of 15% to 20% of the mass of the mixed raw materials to obtain a wet material; (3) feeding the wet material into a mud mill for mixing, thereby obtaining a mud material with a plasticity index of 9-12; (4) feeding the above-mentioned clay material into a vacuum extruder and molding it through a machine mouth die. During extrusion, the titanate graphene mixed solution is dynamically and continuously injected into the inner surface of the machine mouth die. After the clay material is extruded, it is cut into corresponding specifications to obtain a wet body. The flow rate of the titanate graphene mixed solution is 2-3 ml / m2; (5) drying the wet green body at a temperature of 40° C. to 150° C. for 4 to 8 hours to obtain a dry green body; (6) sending the dried green body into a firing kiln and sintering it at a temperature of 1000° C. to 1140° C. for 3 to 5 hours; (7) Cool the ceramic plate.

8. The process for preparing a high-strength, corrosion-resistant ecological ceramic plate according to claim 7, characterized in that: The preparation method of the titanate graphene mixed solution in step (4) is: completely dispersing graphene oxide in water, adding a titanate coupling agent and mixing evenly to obtain a mixed solution, wherein the viscosity of the mixed solution at 25° C. is 2000-4000 cps, and the mass ratio of graphene oxide to titanate coupling agent added is 4:1-2.

9. The preparation process of a high-strength corrosion-resistant ecological ceramic plate according to claim 7, characterized in that: The drying method of step (5) is: first drying at 40-50°C for 3-5 hours, then drying at 51-80°C for 0.5-2 hours, and then drying at 81-150°C for 0.5-1 hour. The sintering method of step (6) is: 1-2 hours at 1000-1050°C, and 2-3 hours at 1051-1140°C.

10. The process for preparing a high-strength, corrosion-resistant ecological ceramic plate according to claim 7, characterized in that: The cooling method of step (7) is as follows: the ceramic plate is transferred to a cooling room, the temperature of the ceramic plate is reduced to 300-600°C, the ambient temperature is maintained at 200-300°C for 2-3 hours, the ambient temperature is reduced to 100-200°C for 2-3 hours, and then naturally cooled.

Citation Information

Patent Citations

  • Low-temperature fast-fired environmentally-friendly pottery clay plate prepared from iron ore tailings and preparation method thereof

    CN102795838A

  • Novel environment-friendly and energy-saving curtain wall material prepared by utilizing sludge and waste ceramics and preparation method thereof

    CN103896556A

  • High strength corrosion resistant ceramic plate and preparation technology thereof

    CN105819861A

  • Graphene and stone tailing based foaming light heat insulation board and preparation method thereof

    CN107721453A

  • Ceramic plate for indoor wall decoration and extrusion molding equipment

    CN115259831A